A Kinematic Analysis of Prey-Capture Prone Jumping by the Barred Mudskipper (Periopthalmus argentilineatus) - Matthias, William (Université d'Ottawa / University of Ottawa, 2024)
Mudskippers are amphibious fish that have developed multiple effective means of terrestrial locomotion. One of these modes of locomotion is the “prone jump”, a jumping motion in which the fish launches itself forwards by coiling and rapidly extending its tail against the ground. Mudskippers utilize this jumping motion to accomplish tasks such as prey-capture and traversal of the environment. To move and hunt effectively they must have some control over the direction in which they are jumping. Here, I define the kinematics of the prey-capture prone jump and then determine how mudskippers adjust the kinematics to produce different jump trajectories. To test how mudskippers control jump trajectory, highspeed cameras were used to capture the three-dimensional movement of mudskippers performing prey-capture prone jumps for food held in various positions. First, initial body position, food position and resultant jump direction are related. Mudskippers were found to rapidly adjust multiple aspects of their initial body position relative to the food and their tail coiling side before the jump. Second, mudskippers were found to increase the maximum speed and acceleration of their jumps (primarily in the vertical direction) when food was positioned farther away or higher above the horizon. Lastly, mudskippers were occasionally observed changing body conformation in the air. These movements were hypothesized to contribute to jump accuracy by altering course trajectory in the air. However, all the jumps analyzed in this study were successful and had initial ground reaction forces and resultant take-off angles that resulted in a ballistic trajectory that did not require aerial course correction to hit the food target. Future analysis of failed jump attempts would be required to confirm the consequence of aerial course correction in these animals.
Keywords: Mudskipper; Prone jump; Kinematics; Trajectory